Children's Oncology Group's 2013 blueprint for research: Radiation oncology. Issue 6 (19th December 2012) - Merchant, Thomas E.; Hodgson, David; Laack, Nadia N.I.; Wolden, Suzanne; Indelicato, Danny J.; Kalapurakal, John A.; ,
Abstract Radiation therapy (RT) is used to treat children with CNS tumors, solid tumors or Hodgkin lymphoma. Pediatric radiation oncologists have provided critical input into the development and implementation of concepts for clinical trials to further define the modality's role and test newer methods to reduce side effects or intensify therapy. The quality of pediatric oncology clinical trials that include radiation therapy is linked to the quality of guidelines. Radiation oncology is an adult medical specialty; thus, pediatric radiation oncologists are uniquely positioned to work with adult cancer investigators in the reorganized US National Cancer Institute Clinic Trials Network. Pediatr Blood Cancer 2013; 60: 1037–1043. © 2012 Wiley Periodicals, Inc.